THF-induced emission enhancement and reversible stimulus response of a tetraphenylethylene luminogen dependent ESIPT mechanism. (December 2019) - Zeng, Xu; Yu, Zian; Wang, Fan; Wang, Xiangmeng; Wang, Chenxia; Lu, Hongguang; Wang, Qiusheng
Abstract: A tetraphenylethene (TPE) derivative tetra(3-1 H -benzo[ d ]imidazol-2-yl) -4-hydroxyphenyl)ethene (TBIHPE) which exhibits crystallization-induced emission enhancement (CIEE) induced by tetrahydrofuran (THF) and reversible fluorescence shifting upon HCl fuming and heating or NH3 fuming was prepared. The CIEE and reversible fluorescence shift process were controlled by imino group and tertiary amine group of 2-(2′-Hydroxyphenyl)benzimidazole (HBI) moiety, respectively. The intermolecular hydrogen bonds between THF and imino group have been observed by single-crystal X-ray structural analysis, which changed the excited-state intramolecular proton transfer (ESIPT) process of TBIHPE, and induced the CIEE phenomena. The fluorescence emission peak of TBIHPE shows blue shift upon HCl fuming stimuli in solid state. Moreover, the fluorescence emission of HCl fumed TBIHPE solid can recover by heating or fuming in NH3 vapors. Based on the results, the relationship between photophysical properties and protonation-deprotonation stimuli was discussed. Graphical abstract: Image 1 Highlights: We synthesized a novel tetraphenylethene derivative TBIHPE. TBIHPE was found to be AEE-active. TBIHPE exhibited CIEE properties. The fluorescence emission of TBIHPE could be shifted by external stimuli.